Correction: Metal-free [2+2+1] cycloaddition polymerization of alkynes, nitriles, and oxygen atoms to functional polyoxazoles. Issue 4 (11th January 2021) - Dong, Lichao; Lan, Tian; Liang, Yin; Guo, Shifeng; Zhang, Hao
Abstract : Correction for 'Metal-free [2+2+1] cycloaddition polymerization of alkynes, nitriles, and oxygen atoms to functional polyoxazoles' by Lichao Dong et al., RSC Adv., 2020, 10, 24368–24373, DOI: ; 10.1039/D0RA04249H .